1986
DOI: 10.1210/jcem-63-3-785
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Calcitonin in Primary Hyperparathyroidism: Failure of C-Cell Response to Sustained Hypercalcemia*

Abstract: An acute increase in serum calcium stimulates calcitonin (CT) secretion, but the effects of chronic hypercalcemia are controversial. Histopathological studies have shown C-cell hyperplasia in primary hyperparathyroidism (1 degree HPT), although circulating levels of CT have been variously reported to be normal, elevated, or depressed. We reexamined this relationship using CT RIA in conjunction with a silica extraction technique that conveys improved sensitivity and specificity for monomeric CT. Nine men and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

1989
1989
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 17 publications
2
9
0
1
Order By: Relevance
“…The relationship between CT and hypercalcemia revealed some discrepancies: if an acute increase of serum calcium was clearly demonstrated to stimulate CT secretion, the effect of chronic hypercalcemia on CT secretion remains unclear [2,6,7,8,9,10,11,12]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The relationship between CT and hypercalcemia revealed some discrepancies: if an acute increase of serum calcium was clearly demonstrated to stimulate CT secretion, the effect of chronic hypercalcemia on CT secretion remains unclear [2,6,7,8,9,10,11,12]. …”
Section: Discussionmentioning
confidence: 99%
“…Although most of the authors found normal CT levels [7,8], others have reported basal elevated CT: in about 50% of cases in a series of 28 patients, and in men only from another series of 55 patients [9,10,11]. However, all these studies were done in a small series of patients and used polyclonal CT radioimmunoassays which are not specific of the mature CT monomer, which should explain the reported high CT levels in these series.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Como a CT é um hormônio liberado quando ocorre aumento dos níveis de Ca no plasma, seria de se esperar níveis elevados desse peptídio nos pacientes que se encontravam hipercalcêmicos. Mas, ao contrário, todos apresentavam-se com níveis normais ou indosáveis de CT, confirmando, assim, a perda da resposta das células C à hipercalcemia crônica já descrita por outros pesquisadores 26,27 . Estudos in vitro demonstram haver uma diminuição da sensibilidade das células C a níveis suprafisiológicos de Ca, após exposição prolongada 28 .…”
Section: Methodsunclassified
“…Effects of free Ca2+ concentration on C cell number and growth As the relationship between C cell behavior and serum Ca 2+ level has been controversial (Zabel 1976;Tiegs et al 1986;MartinLacave et al 1998), we examined the number of calcitonin-positive C cells at various free Ca 2+ concentrations. The free Ca 2+ of the complete medium was 0.39 mM (Sugihara et al 1985).…”
Section: Immunohistochemistrymentioning
confidence: 99%